Pendekatan Feminis dalam Kajian Islam - Afrohatul Laili; M. Wildanul Ulum; M. Faizurrizqi Al-Farisi AD (Comprehensive Journal of Islamic Studies, 2024)
One of the interesting studies in Islam is the existence of women. Along with the increasing discussion about women in the last decade, contemporary Islamic discourse directly or indirectly certainly touches on this actual problem. Throughout history, issues surrounding women have been discussed repeatedly, both by secular thinkers and religious scholars. The debate about gender has become a big industry for the world of education, especially in Islamic studies and is very interesting to discuss. Because of this, the term feminism emerged, the issue of which was the emergence of this understanding in the form of fighting for equal gender rights and demanding women's access to public life. This research uses normative research because the research uses library materials as the main data for analyzing cases. This research specifically examines feminist approaches in Islamic studies. Feminism is a movement of feminists who hold the view that women are discriminatory, treated unfairly, therefore it is not in accordance with the principles of justice and the basic principles of Islam. The feminist approach in the study of religion is nothing but a critical transformation of existing theoretical reviews using gender as the main analytical category. The basics of feminist thinking are that the door to ijtihad remains open, freeing oneself from attachment to the past, changing times can give birth to changes in teachings, the superiority of reason over revelation, and justice as the basis of benefit.